National Dietary Guidelines of Greece for children and adolescents: a tool for promoting healthy eating habits. Issue 14 (21st May 2019) - Kastorini, Christina-Maria; Critselis, Elena; Zota, Dina; Coritsidis, Alexandra L; Nagarajan, Meera K; Papadimitriou, Eleni; Belogianni, Katerina; Benetou, Vassiliki; Linos, Athena; ,
Abstract: Objective: Dietary guidelines are an essential policy tool for facilitating optimal dietary patterns and healthy eating behaviours. We report: (i) the methodological approach adopted for developing the National Dietary Guidelines of Greece (NDGGr) for Infants, Children and Adolescents; and (ii) the guidelines for children aged 1–18 years. Design: An evidence-based approach was employed to develop food-based recommendations according to the methodologies of the WHO, FAO and European Food Safety Authority. Physical activity recommendations were also compiled. Food education, healthy eating tips and suggestions were also provided. Setting: The NDGGr encompass food-based nutritional and physical activity recommendations for promoting healthy dietary patterns and eating behaviours and secondarily to serve as a helpful tool for the prevention of childhood overweight and obesity. Results: The NDGGr include food-based recommendations, food education and health promotion messages regarding: (i) fruits; (ii) vegetables; (iii) milk and dairy products; (iv) cereals; (v) red and white meat; (vi) fish and seafood; (vii) eggs; (viii) legumes; (ix) added lipids, olives, and nuts; (x) added sugars and salt; (xi) water and beverages, and (xii) physical activity. A Nutrition Wheel, consisting of the ten most pivotal key messages, was developed to enhance the adoption of optimal dietary patterns and a healthy lifestyle. The NDGGr additionally provide recommendations regarding the optimal frequency and serving sizes of main meals, based on the traditional Greek diet. Conclusions: As a policy tool for promoting healthy eating, the NDGGr have been disseminated in public schools across Greece.